Identifying Factors Affecting the Competitiveness of Urban Tourism Purposes (Case Study: Ardabil City) - Abbas Minai; Rahim Heydari Chianeh; Shahrivar Rustai (تحقیقات کاربردی علوم جغرافیایی)
the purpose of this study was to identify factors affecting the competitiveness of tourism destinations. The present study is of applied purpose and of descriptive-analytical method. The required data for the study were collected in two forms: library and field (questionnaire). The statistical population of the study consisted of incoming tourists to Ardebil city. Due to the lack of accurate statistics on the number of incoming tourists the Cochran formula was used to determine the sample size for an unlimited population. The sample size was 384 people. It was a simple accident. In order to check the validity of the questionnaire, the validity of the questionnaire was confirmed in two stages of face and face validity through the opinion of professors and experts, and divergent validity was confirmed by calculating the extracted mean variance index (AVE). The reliability of the questionnaire was measured by Cronbach's alpha and the combined reliability coefficient (cr). The results of Cronbach's alpha and combined reliability of the questionnaire confirmed the validity of the questionnaire. Spss and lisrel software were used for data analysis. The findings of this study showed that creativity and sustainability of tourism destinations have a positive and significant effect on the competitiveness of urban tourism destinations. The results also showed that the impact of sustainability of tourism destinations on the competitiveness of tourism destinations is more than the creativity of tourism destinations